Implementation of precision medicine in treating non-communicable diseases: a systematic review - Liang, Shuang; Kennedy, Elizabeth; Gale, Nyree; Watson, Paul; Ramanathan, Mahitha; Shinde, Arya; McKay, Skye; Torres-Robles, Andrea; Li, Zhicheng; Chan, Jeffery; Jones, Helen; Ballinger, Mandy L.; et al. (Journal of translational medicine, 2025)
Background Non-communicable diseases (NCDs) are a major global health and economic burden. Precision medicine has merged as a promising approach for treating NCDs by tailoring health interventions to individual profiles. Despite rapid advances, its effective implementation remains slow. This systematic review aimed to examine the implementation landscape for delivering precision medicine interventions, services, or programs for NCDs, focusing on barriers, facilitators, strategies, and outcomes. Methods Comprehensive searches were performed in PubMed, Embase, CINAHL, and Web of Science until November 2024. The search strategy comprised of four key concepts, i.e. precision medicine, NCDs, implementation, and public health. Articles published from 2014 onwards were included. Extracted data included study characteristics, populations, precision medicine intervention details, and information related to implementation. Relevant data were coded to implementation science frameworks and taxonomies. These included the updated Consolidated Framework for Implementation Research (CFIR 2.0), Expert Recommendations for Implementing Change (ERIC), and Proctor’s outcomes framework. The QuADs tool was used to assess the risk of bias of included studies. Results A total of 10,039 records were identified, with 8,684 abstracts and 463 full texts screened. Of these, 68 studies met the inclusion criteria. While 64 studies reported implementation determinants [i.e. barriers ( n = 61) and/or facilitators ( n = 40)], approximately two-thirds proposed or implemented strategies that were primarily based on intuition. Key barriers identified included ‘access to knowledge and information’ ( n = 34) and ‘work infrastructure’ ( n = 21) within the Inner Setting, and ‘financing’ ( n = 20) within the Outer Setting. While financial burdens were clearly attributed to patients and healthcare settings, there was less clarity and strategic direction regarding potential funding sources to support implementation strategies. Implementation Outcomes were reported in 46 instances, with Adoption being the most frequent. Service Outcomes, particularly Effectiveness, were generally positive, as were patient outcomes, primarily, mortality and morbidity. Conclusion Despite growing interest in precision medicine for treating NCDs, implementation evidence remains theoretically fragmented, making it difficult to identify implementation success patterns. Future efforts adopting targeted strategies and robust outcome evaluation, guided by implementation science, are needed to support effective integration of precision medicine into routine healthcare.